Molecular and cellular issues of KMT2A variants involved in Wiedemann-Steiner syndrome. (January 2018) - Lebrun, Nicolas; Giurgea, Irina; Goldenberg, Alice; Dieux, Anne; Afenjar, Alexandra; Ghoumid, Jamal; Diebold, Bertrand; Mietton, Léo; Briand-Suleau, Audrey; Billuart, Pierre; Bienvenu, Thierry
Abstract Variants inKMT2A, encoding the histone methyltransferase KMT2A, are a growing cause of intellectual disability (ID). Up to now, the majority ofKMT2A variants are non-sense and frameshift variants causing a typical form of Wiedemann–Steiner syndrome. We studiedKMT2A gene in a cohort of 200 patients with unexplained syndromic and non-syndromic ID and identified four novel variants, one splice and three missense variants, possibly deleterious. We used primary cells from the patients and molecular approaches to determine the deleterious effects of those variants onKMT2A expression and function. For the putative splice variant c.11322-1G>A, we showed that it led to only one nucleotide deletion and loss of the C-terminal part of the protein. For two studiedKMT2A missense variants, c.3460C>T (p.(Arg1154Trp)) and c.8558T>G (p.(Met2853Arg)), located at the cysteine-rich CXXC domain and the transactivation domain of the protein, respectively, we found altered KMT2A target genes expression in patient's fibroblasts compared to controls. Furthermore, we found a disturbed subcellular distribution of KMT2A for the c.3460C>T mutant. Taken together, our results demonstrated the deleterious impact of the splice variant and of the missense variants located at two different functional domains and suggested reduction of KMT2A function as the disease-causing mechanism.